1995
DOI: 10.1016/0092-8674(95)90082-9
|View full text |Cite
|
Sign up to set email alerts
|

par-1, a gene required for establishing polarity in C. elegans embryos, encodes a putative Ser/Thr kinase that is asymmetrically distributed

Abstract: The first cleavage of C. elegans is asymmetric, generating daughter cells with different sizes, cytoplasmic components, and fates. Mutations in the par-1 gene disrupt this asymmetry. We report here that par-1 encodes a putative Ser/Thr kinase with similarity to kinases from yeasts and mammals. Two strong alleles have mutations in the kinase domain, suggesting that kinase activity is essential for par-1 function. PAR-1 protein is localized to the posterior periphery of the zygote and is distributed in a polar f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
583
1
17

Year Published

1996
1996
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 978 publications
(615 citation statements)
references
References 35 publications
11
583
1
17
Order By: Relevance
“…Some of these AMPK-related kinases are the MAP/microtubule affinity-regulating kinases (MARK1, MARK2, MARK3 and MARK4) involved in microtubule stabilization, which may be related with the proposed role of LKB1 in cell polarity. Supporting this, LKB1 is homologous to the Par-4 genes of Caenorhabditis elegans, essential for establishing anterior-posterior (A-P) axis during embryonic development (Guo and Kemphues, 1995), and to the Drosophila lkb1, also required for the early A-P polarity of the oocyte, and for the repolarization of the oocyte cytoskeleton that defines the embryonic A-P axis (Martin and St Johnston, 2003). In mammalians, LKB1 induces complete polarization of intestinal epithelial cells in a cellautonomous fashion (Baas et al, 2004).…”
Section: Lkb1 As An Energetic Checkpoint Controllermentioning
confidence: 93%
“…Some of these AMPK-related kinases are the MAP/microtubule affinity-regulating kinases (MARK1, MARK2, MARK3 and MARK4) involved in microtubule stabilization, which may be related with the proposed role of LKB1 in cell polarity. Supporting this, LKB1 is homologous to the Par-4 genes of Caenorhabditis elegans, essential for establishing anterior-posterior (A-P) axis during embryonic development (Guo and Kemphues, 1995), and to the Drosophila lkb1, also required for the early A-P polarity of the oocyte, and for the repolarization of the oocyte cytoskeleton that defines the embryonic A-P axis (Martin and St Johnston, 2003). In mammalians, LKB1 induces complete polarization of intestinal epithelial cells in a cellautonomous fashion (Baas et al, 2004).…”
Section: Lkb1 As An Energetic Checkpoint Controllermentioning
confidence: 93%
“…Partitioning-defective (par) genes, which were originally identified in Caenorhabditis elegans, regulate asymmetric division of the zygote (Kemphues et al 1988;Guo and Kemphues 1995;Watts et al 1996;Tabuse et al 1998). Subsequent studies have revealed that the gene products are part of an evolutionarily conserved PAR-aPKC system involved in cell polarity in various biological contexts.…”
Section: Introductionmentioning
confidence: 99%
“…In one sense, the story started with a test of the efficacy of antisense RNA in Caenorhabditis elegans. Sense RNA was a logical control but, interestingly, antisense and sense RNAs caused specific silencing of the targeted gene to similar degrees [2]. What might have been considered a failed experiment, in retrospect, built the foundation for coalescence in the field of gene silencing.…”
mentioning
confidence: 99%